Campur Kode Dan Majas Sarkasme Pada Bahasa Dakwah K.H. Anwar Sahid - Joko Purwanto, Lanjar, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Prof. Dr. Markhamah, M.Hum (2017)
This study has four goals. 1) Describe the use of mixed code in languages that Da'wah k. H Anwar Sahid. 2) Describe use of stylistics in the language of the Da'wah k. H Anwar Sahid. 3) Describe the relationship between mix code and style language on religious propagation Anwar Sahid. 4) Knowing the implementation of language learning in Indonesia. This research was conducted with qualitative methods. The object of study in this research Da'wah is k.h. Anwar Sahid. The data in this study is a mix of code and the style of the language in the language of the Da'wah k. H Anwar Sahid. The data source in this research Da'wah language k. H Anwar Sahid.The technique of data collection in this research is the technique of simak and note. After data collection techniques and then determine the techniques of data analysis using the method of indeterminate and agih methods. The results of this research it can be concluded that. 1) The usage mix code overall totaled 48 data consists of a mix of code words consists of 7 noun, verb, 4 adjectives, adverbs, 7 conjunctions. Mix the code phrase consists of 20 data. 2) The use of sarcasm Majo totaled 12 data that strongly support on Da'wah k. H Anwar Sahid. mix the code clause consists of 4. 3) The relationship between mix code and style language in Da'wah K. H Anwar Sahid also reinforces the use of mixed code. The style of language used in the study is precisely as a means to attract the participants payroll to always follow the storyline of travelling. 4) The presence of mixed code as used in event propagation k. H Anwar Sahid is very useful to give the appeal against students or students in order to listen to the explanations from the teacher.